Associations Between Burnout and Mental Disorder Symptoms Among Nurses in Canada. Issue 3 (September 2021) - Stelnicki, Andrea M.; Jamshidi, Laleh; Angehrn, Andréanne; Hadjistavropoulos, Heather D.; Carleton, R. Nicholas
Background: Nurses appear to be at a greater risk of burnout compared to other medical professionals. Higher levels of burnout are significantly associated with higher levels of anxiety, stress, and depression symptoms. Purpose: The current study was designed to estimate levels of burnout among Canadian nurses, examine the association between burnout and mental disorder symptoms, and identify characteristics that may increase the risk for reporting symptoms of burnout. Method: Canadian nurses ( n = 3257; 94.3% women) were surveyed online in both English and French. The survey assessed current symptoms of burnout and mental disorders (i.e., Posttraumatic Stress Disorder, Major Depressive Disorder, Generalized Anxiety Disorder, Panic Disorder). Results: Most nurses (63.2%) reported at least some symptoms of burnout and many (29.3%) reported clinically significant levels of burnout. Age and years of service were the only demographic variables that explained burnout rates. Participants reporting clinically significant levels of burnout were significantly more likely than participants with no burnout to screen positive for all mental disorders, but particularly for Major Depressive Disorder. Conclusions: Monitoring burnout may be an effective way to identify nurses at risk of developing symptoms of mental disorders. Younger and early-career nurses are an important group to target for prevention programs.